Comparative study of maternal and foetal outcome in instrumental vaginal deliveries - Ahmed, Mariyam S.; Bhalerao, Anand N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The art of instrumental vaginal delivery is fading as more and more obstetricians resort to caesarean sections. Instrumental deliveries are deliveries accomplished with the use of vacuum device or forceps. Once either is applied to the foetal head, outward traction generates forces that augment maternal pushing to deliver the foetus vaginally. Objective of present study was to compare the maternal and foetal outcome of forceps versus ventouse delivery. Methods: It was a prospective observational study conducted in Sassoon Hospital between January 2014 to January 2015. A total of 120 cases, 60 each of forceps and ventouse, admitted in labour room were included in the study. Maternal and neonatal morbidity were compared in terms of perineal lacerations, episiotomy extension, post-partum haemorrhage, Apgar score, instrumental injuries. Chi square test and z test of proportion was used to analyze the data. Results: Maternal morbidity, namely episiotomy extension as well as perineal tears were significant in the forceps group. With regards to neonatal morbidity, no statistically significant difference was noted. Conclusions: Vacuum and forceps should remain appropriate tools in the armamentarium of the modern obstetrician. However, ventouse may be chosen first (if there is no foetal distress) as it is significantly less likely to injure the mother.